Preparation and application of ZrO2–SiO2 complex oxide for efficient biocrude generation by hydrothermal liquefaction of Spirulina. (1st June 2022) - Wang, Shaobo; Zeng, Fangang; Liu, Yanwei; Meng, Yanghao; Wang, Wenjia; Liu, Chang; Zhang, Jinglai; Du, Hongbiao; Li, Jie
Abstract: Catalysts act a pivotal part in hydrothermal liquefaction (HTL), which is a efficient technology for converting biomass into bioenergy. Herein, atom-doped ZrO2–SiO2 complex oxide catalysts were prepared for HTL of Spirulina  to produce biocrude. In this study, sol–gel method was adopted to prepare the catalysts. Calcination temperature, surfactant type and dosage, ratio of SiO 2  to ZrO 2  were analyzed for optimizing biocrude yield. Physicochemical properties of ZrO2–SiO2 catalysts were conducted by X-ray diffraction, thermogravimetric analysis, N2 adsorption–desorption and infra-red spectroscopy of pyridine adsorption. The result showed that the catalysts that calcinated at 700 °C with the ratio of SiO 2 : ZrO 2  = 10:1, 5 g polyethylene glycol applied in the sol precursor achieved the best performance: specific surface area reached 461.86 m 2 g −1 and the density of total acid site was up to 53.98 mmol g −1, thereby it provided the highest biocrude yield as 55.8%, which contained the largest hydrocarbon content. Accordingly, ZrO2–SiO2 demonstrated promising catalyst ability in the field of HTL and could inspire related researchers screening HTL catalysts from certain aspects. Highlights: Catalytic ability of SiO 2  for biomass HTL was improved by ZrO 2  doping. The yield of biocrude and the energy recovery ratio were improved significantly. ZrO2–SiO2 complex oxide catalyst with large specific surface area was prepared. Mechanism of PEG in ZrO2–SiO2 catalyst fabrication by sol–gel method was explored. The optimized biocrude yield achieved 55.8%.